INCREASED PUBLIC AWARENESS ABOUT HEALTH PROTOCOLS DURING THE PANDEMIC: PENINGKATAN KESADARAN MASYARAKAT TENTANG PROTOKOL KESEHATAN DI MASA PANDEMI - Nafiudin Nafiudin; Dian Maulita (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2022)
The purpose of this service activity is to increase public awareness about the importance of complying with health protocols during the pandemic which has entered the new normal era. In general, people still do not understand the dangers of Covid-19 and how to prevent it in this new normal era. This is due to the lack of knowledge possessed by the community and the lack of dissemination of education regarding health protocols so people tend to ignore these regulations. With the holding of socialization and education programs related to Covid-19 which include an introduction, distribution, handling, and prevention, it is hoped that this will increase public awareness of the importance of complying with health protocols that can indirectly prevent the spread of Covid-19 in the new normal era. This community service activity is a form of concern for the surrounding community so that public awareness of compliance with health protocols increases. Therefore, there is a need for new habit education, especially in maintaining health by the protocols applicable in Indonesia. The education provided is in the form of digital education about the adaptation of Covid-19 in the new normal era which is delivered through social media in the form of videos or posters, how to make cloth masks, how to make disinfectants, and spray hand sanitizers. The target of this service activity program is to increase public awareness of the importance of health and prevent the spread of Covid-19 in the new normal by complying with health protocols